Patients with perianal Crohn's fistulas experience delays in accessing anti‐TNF therapy due to slow recognition, diagnosis and integration of specialist services: lessons learned from three referral centres. (14th April 2018) - Lee, M. J.; Freer, C.; Adegbola, S.; Elkady, S.; Parkes, M.; Hart, A.; Fearnhead, N. S.; Lobo, A. J.; Brown, S. R.
Abstract: Aim: Crohn's anal fistula should be managed by a multidisciplinary team. There is no clearly defined 'patient pathway' from presentation to treatment. The aim of this study was to describe the patient route from presentation with symptomatic Crohn's anal fistula to starting anti‐tumour necrosis factor (anti‐TNF) therapy. Method: Case note review was undertaken at three hospitals with established inflammatory bowel disease services. Patients with Crohn's anal fistula presenting between 2010 and 2015 were identified through clinical coding and local databases. Baseline demographics were captured. Patient records were interrogated to identify route of access, and clinical contacts during the patient pathway. Results: Seventy‐nine patients were included in the study, of whom 54 (68%) had an established diagnosis of Crohn's disease (CD). Median time from presentation to anti‐TNF therapy was 204 days (174 vs 365 days for existing and new diagnosis of CD, respectively; P = 0.019). The mean number of surgical outpatient attendances, operations and MRI scans per patient was 1.03, 1.71 and 1.03, respectively. Patients attended a mean of 1.49 medical clinics. Seton insertion was the most common procedure, accounting for 48.6% of all operations. Where care episodes ('clinical events per 30 days') were infrequent this correlated with prolongation of the pathway ( r = −0.87; P < 0.01). Conclusion: This study highlights two key challenges in the treatment pathway: (i) delays in diagnosis of underlying CD in patients with anal fistula and (ii) the pathway to anti‐TNF therapy is long, suggesting issues with service design and delivery. These should be addressed to improve patient experience and outcome.